DETERMINATION OF CHARRING RATE OF OAK WOOD - Párničanová, Alena; Zachar, Martin; Kačíková, Danica; Zacharová, Lucia (Acta Facultatis Xylologiae Zvolen, 2023)
This paper deals with the determination of selected fire properties of oak wood, i.e., charring rate, which is used in practice to model and investigate the fire causes. Thermal loading was carried out using a measuring apparatus described in Utility Model No. 9373 registered by the Industrial Property Office of the Slovak Republic. Oak wood samples with dimensions of 40 × 50 × 50 mm (l × w × t) were thermally loaded by a heat flux of 15, 20, 25 and 30 kW·m-2, using a ceramic infrared heater. Two methods of determination of the charring rate, based on reaching the temperature of 300 ⁰C in individual depths in a specific time and according to the thickness of the charred layer formed in a time interval of 1800 s measured using a caliper were compared. Both methods confirmed that the charring rate is increasing with increasing thermal loading. The charring rate determined based on the temperature of 300 ⁰C ranged from 0.65 to 0.88 mm·min-1. According to the second method, the charring rate reached values from 0.41 to 0.86 mm·min-1. More accurate results were achieved by applying the method of determination of the charring rate based on the charred layer measured by a caliper. However, the method of determination of the charring rate using thermocouples can be considered less subjective because the temperature is measured automatically, using thermocouples compared to manual measurement using a caliper. The obtained results can be used as input data for computer-supported modeling of indoor fires.